Design of an Intelligent MEMS Safety and Arming Device with a Condition Feedback Function - Kexin Wang; Tengjiang Hu; Yulong Zhao; Wei Ren; Yifei Wang (Micromachines, 2023)
A safety and arming device with a condition feedback function has been designed in this article to improve the intelligence and safety of ignition devices. The device achieves active control and recoverability by virtue of four groups of bistable mechanisms which consist of two electrothermal actuators to drive a semi-circular barrier and a pawl. According to a specific operation sequence, the barrier is engaged by the pawl at the safety or the arming position. The four groups of bistable mechanisms are connected in parallel, and the device detects the contact resistance generated by the engagement of the barrier and pawl by the voltage division of an external resistor to determine the parallel number of the mechanism and give feedback on the device’s condition. The pawl as a safety lock can restrain the in-plane deformation of the barrier in the safety condition to improve the safety function of the device. An igniter (a NiCr bridge foil covered with different thicknesses of Al/CuO films) and boron/potassium nitrate (B/KNO3, BPN) are assembled on both sides of the S&A device to verify the safety of the barrier. The test results show that the S&A device with a safety lock can realize the safety and arming functions when the thickness of the Al/CuO film is set to 80 μm and 100 μm.